PERADILAN AGAMA DI INDONESIA; GEJALA KEISLAMAN DALAM PENERAPAN HUKUM ISLAM (Suatu Tinjauan Transformasi Hukum Islam Ke Dalam Sistem Peradilan) - M. Husni Mubarok dan Aristono (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2013)
The promulgation of Law No 7 of 1989 on Religious Courts, a milestone in the transformation of early Islamic law into national legislation in the judicial system in Indonesia. Religious Court is the process of judicial based on Islamic law for Muslims undertaken by the Religious Court and Religious High Court. The existence of the Religious Courts in the Indonesian national judicial system is one of judicial powers in Indonesia. In addition to the Religious Courts, Indonesia also recognized three other courts that have the same and equal position with the different authority, they are the General Court, Military Court, and State Administrative Court. Lihat juga: https://www.surreyhillschallenge.com/ Religious Courts can be viewed as a symptom of Islam because it can reveal many aspects of life especially in social issues. Indications of the Islamic symptoms are the enactment of Law No. 7 of 1989 on Religious Courts, and put it into the country's judicial system, Law No. 1 of 1974 on Marriage, and the Compilation of Islamic Law (KHI), all of which are in the realm of law in Indonesia, the concretization of a form of Islam and a product of applied normative law must be obeyed by the people of its adherents, as the living law. Bandingkan pula: https://www.adenomyosisadviceassociation.org/hysterectomy dan https://www.fortyouncewines.com/ Keywords: Religious Courts, Islamic Symptoms, Transformation of Islamic Law